2017
DOI: 10.1038/s41467-017-01371-0
|View full text |Cite
|
Sign up to set email alerts
|

An automated platform for high-throughput mouse behavior and physiology with voluntary head-fixation

Abstract: Recording neural activity during animal behavior is a cornerstone of modern brain research. However, integration of cutting-edge technologies for neural circuit analysis with complex behavioral measurements poses a severe experimental bottleneck for researchers. Critical problems include a lack of standardization for psychometric and neurometric integration, and lack of tools that can generate large, sharable data sets for the research community in a time and cost effective way. Here, we introduce a novel mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 21 publications
(25 reference statements)
0
78
0
Order By: Relevance
“…We speculate that as experimenters gain more experience, the differences in learning times will decrease. Indeed, one approach to standardizing learning rates might be to introduce full automation in behavioral training, reducing the need for human intervention [e.g., Scott et al, 2013 ;Poddar et al, 2013 ;Aoki et al 2017 ]. We anticipate that approaches such as self-head fixation, live-in home cage training systems, and individualized dynamic training methods [ Roy et al, 2018 ] used independently or in combination may reduce variability in learning rates.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that as experimenters gain more experience, the differences in learning times will decrease. Indeed, one approach to standardizing learning rates might be to introduce full automation in behavioral training, reducing the need for human intervention [e.g., Scott et al, 2013 ;Poddar et al, 2013 ;Aoki et al 2017 ]. We anticipate that approaches such as self-head fixation, live-in home cage training systems, and individualized dynamic training methods [ Roy et al, 2018 ] used independently or in combination may reduce variability in learning rates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it cannot be excluded the possibility that major differences exist, between mouse and rat visual cortex, in terms of high-order processing of shape information. In fact, despite some recent efforts (Aoki et al, 2017;Yu et al, 2018), mouse visual perception is still largely unexplored, and it remains unknown whether mice are able to perform those perceptual tasks, recently demonstrated in rats (Zoccolan et al, 2009;Tafazoli et al, 2012;Alemi-Neissi et al, 2013;Vinken et al, 2014;Rosselli et al, 2015;De Keyser et al, 2015;Djurdjevic et al, 2018), that should specifically engage the ventral stream.…”
Section: #### Figure 11 Near Here ####mentioning
confidence: 99%
“…In a previous study head-fixation was found to be aversive, but with training and habituation stress recedes and rodents can even be trained to restrain themselves (Aoki et al, 2017;Murphy et al, 2016;Scott et al, 2013) . For this reason we present the results as an interaction that occurs in the context of head-fixation and caution that the observed brain dynamics may not be entirely reflective of true natural social touch behavior.…”
Section: Discussionmentioning
confidence: 90%